Educational psychology - Peterson, Harvey Andrew, 1873-1947 (Macmillan Co., 1948)
"The early period of psychology abstracted the subject matter from life in the interests of scientific accuracy, but there was a loss of popular interest. Recently there has been a reverse tendency to retain much of the social setting in the effort to make psychology more useful. The authors have shared in the belief that Educational Psychology should stress education in cooperative effort more and competition less, and that much more contact with life should be retained in the teaching of the subject than has been the case in the past. In fact it might be said, that mere contact is not enough; that it is practicable to leave the psychological facts in their social setting at first and still make them clear and accurate. Accordingly, (i) cooperative group learning has been given a greater place than it has usually had, especially in Chapter i, in which the social environment of youth has been described; in Chapter 4, where the experimental evidence for the effectiveness of cooperative learning has been assembled and compared with individual learning; and in Chapter 5, "Learning Predominantly Social," where examples are given showing how learning in the classroom has been made more social and cooperative. Other features of the book that contribute to its strength as a teaching text are: (2) the laws of learning meaningful ideas, such as the importance of organization, the role of first-hand experience and meaning in understanding, the necessity of participation by the class, and the importance of reducing what has been learned to abstract form, have been given first place, and the laws of association relegated to rote learning (pages 256-257) where alone they play a leading part. Preface (3) Case studies of teaching have been given a bolder and more functional treatment in their relation to the learning process than has been done heretofore. If the teacher believes in connecting Educational Psychology with the observation of teaching, he is in a position to accept this innovation as worth a trial, for verbal reports of teaching are certainly only supplementary to the observation of teaching. The use of stenographic reports of teaching in connection with the teaching of Educational Psychology and other professional courses has been tried before, and has not had much success, but it has never been given a fair trial. Either the samples of teaching were poor or they were not connected with the study of the principles of learning. In the present text most of the case studies are examples of teaching above the average of the public schools, for they were the best of one hundred from which verbatim reports were obtained. Many of them were arranged to illustrate principles of teaching. They are taught in connection with the study of the principles of learning to be found in Chapters 5 and 6 and 7-10"--Preface. (PsycINFO Database Record (c) 2014 APA, all rights reserved)